Can Leaf Water Content Be Estimated Using Multispectral Terrestrial Laser Scanning? A Case Study With Norway Spruce Seedlings - Junttila, Samuli; Sugano, Junko; Vastaranta, Mikko; Linnakoski, Riikka; Kaartinen, Harri; Kukko, Antero; Holopainen, Markus; Hyyppä, Hannu; Hyyppä, Juha (Frontiers in Plant Science, 2018)
Changing climate is increasing the amount and intensity of forest stress agents, such as drought, pest insects, and pathogens. Leaf water content (LWC) is an early indicator of tree stress that provides timely information about the health status of forests. Multispectral terrestrial laser scanning (MS-TLS) measures target geometry and reflectance simultaneously, providing spatially explicit reflectance information at several wavelengths. LWC and leaf internal structure affect leaf reflectance in the shortwave infrared region that can be used to predict LWC with MS-TLS. A second wavelength that is sensitive to leaf internal structure but not affected by LWC can be used to normalize leaf internal effects on the shortwave infrared region and improve the prediction of LWC. Here we investigated the relationship between LWC and laser intensity features using multisensor MS-TLS at 690 nm, 905 nm, and 1550 nm wavelengths with both drought-treated and Endoconidiophora polonica inoculated Norway spruce seedlings to better understand how MS-TLS measurements can explain variation in LWC. In our study, a normalized ratio of two wavelengths at 905 nm and 1550 nm and length of seedling explained 91% of the variation (R 2) in LWC as the respective prediction accuracy for LWC was 0.003 g/cm2 in greenhouse conditions. The relation between LWC and the normalized ratio of 905 nm and 1550 nm wavelengths did not seem sensitive to a decreased point density of the MS-TLS data. Based on our results, different LWCs in Norway spruce seedlings show different spectral responses when measured using MS-TLS. These results can be further used when developing LWC monitoring for improving forest health assessments.